Determination of life background and academic integrity on academic cheating behavior (Case Study of Economic Education Student’s, Faculty of Teacher Training and Education, Lambung Mangkurat University) - Martodiryo, Suratno; Siahaan, Larisma Valentyna; Setiti, Sri (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2022)
This study aims to determine the level of life background and academic integrity possessed by students and their determination of academic cheating behavior. This research is a quantitative study with a correlational design using survey methods. The questionnaire met the validity test with a KMO value of 0.736. The instrument was declared are reliable with a value of 0.863 for the life background, 0.830 for the academic integrity and 0.752 for the academic cheating behavior. Academic cheating behavior that is most often done by students is cheating; students who classified as high cheating behavior as much as 54.5%. Academic Integrity after being controlled by Life Background has a regression coefficient on Academic Cheating Behavior of ry2-1=0.66 with a determination of 43.9%. The correlation coefficient between life background and academic integrity is r12=0.56; p <0.01. The value of the correlation coefficient between academic integrity variables on cheating behavior is ry2 = -0.60; p <0.01. The highest contribution was found in the variable Trust, a simple correlation was ry2 = -0.64; p <0.01, a partial correlation was ry1-2 = -0.51 with a determinant of 25.7%. The correlation coefficient between life background and academic cheating is ry1 = -0.571; p <0.01. The indicator that gave the highest contribution was Peers with a value of ry = -0.56; p <0.01.